Efficiency Optimization of CRISPR/Cas9-Mediated Targeted Mutagenesis in Grape - Ren, Fengrui; Ren, Chong; Zhang, Zhan; Duan, Wei; Lecourieux, David; Li, Shaohua; Liang, Zhenchang (Frontiers in Plant Science, 2019)
Clustered regularly interspersed short palindromic repeats (CRISPR)/Cas system is an efficient targeted genome editing method. Although CRISPR/Cas9-mediated mutagenesis has been applied successfully in grape, few studies have examined the technique’s efficiency. To optimize CRISPR/Cas9 editing efficiency in Vitis vinifera, we surveyed three key parameters: GC content of single guide RNA (sgRNA), variety of transformant cells used, and SpCas9 expression levels in transgenic cell mass. Four sgRNAs with differing GC content were designed to target exon sites of the V. vinifera phytoene desaturase gene. Suspension cells of ‘Chardonnay’ and ‘41B’ varieties were used as the transgenic cell mass. Both T7EI and PCR/RE assays showed that CRISPR/Cas9 editing efficiency increases proportionally with sgRNA GC content with 65% GC content yielding highest editing efficiency in both varieties. Additionally, gene editing was more efficient in ‘41B’ than in ‘Chardonnay.’ CRISPR/Cas9 systems with different editing efficiency showed different SpCas9 expression level, but compared with GC content of sgRNA, SpCas9 expression level has less influence on editing efficiency. Taken together, these results help optimize of CRISPR/Cas9 performance in grape.